Adoption Status of Traditional and Commercial Fish Feeds Among Fish Farmers in the Fish Super Zone of Rupandehi, Nepal - Yadav, Govind; Yadav, Punam; Upadhyaya, Ashish (International Journal of Applied Sciences and Biotechnology, 2026)
This study was conducted from February to July of 2023 in the Fish Superzone of Rupandehi, Nepal, using a semi-structured questionnaire administered to 135 randomly selected respondents. The objectives were to assess the feeding system, the willingness of fish farmers to adopt commercial fish feed, and the factors associated with feed type adoption. Results showed that 69.6% of respondents were using traditional feed, 25.9% both traditional and commercial feed, and 4.4% were using commercial feed exclusively. Among traditional feed users, 83.7% relied solely on mustard oilcake (MOC) and rice bran (RB), with significant variation in blending ratios. Additionally, 92.4% of respondents using traditional feed were unwilling to switch to commercial fish feed, primarily due to high cost (94.7% of responses) and adherence to traditional practices (88.3%). The pond water surface area and gender were found to be significantly associated with the type of feed adopted. This study suggests, providing women-specific training, optimizing nutrients in fish feed through training on blending of locally available inputs for traditional feed with effective pond management, and subsidy programs on feed additives (vitamins, minerals, and probiotics) can improve feeding system.Int. J. Appl. Sci. Biotechnol. Vol 14(1): 1-13.